2022
DOI: 10.1016/j.cardfail.2021.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease-2019 and Heart Failure: A Scientific Statement From the Heart Failure Society of America

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 168 publications
(188 reference statements)
1
12
0
Order By: Relevance
“…Recommendations made in this ECDP are intended to be applied to a broad, unselected population; individualized approaches may be needed for specific populations (eg, those who are pregnant, those with adult congenital heart disease, those with pre-existing heart failure). 13 Finally, although other cardiovascular sequelae exist with COVID-19 (eg, thrombosis), they are not covered in this ECDP.
Figure 1 Scope of the Expert Consensus Decision Pathway on Cardiovascular Sequelae of COVID-19 in Adults PASC = post-acute sequelae of SARS-CoV-2 infection; RTP = return to play; SARS-CoV-2 = severe acute respiratory syndrome coronavirus 2.
…”
Section: Rationalementioning
confidence: 99%
“…Recommendations made in this ECDP are intended to be applied to a broad, unselected population; individualized approaches may be needed for specific populations (eg, those who are pregnant, those with adult congenital heart disease, those with pre-existing heart failure). 13 Finally, although other cardiovascular sequelae exist with COVID-19 (eg, thrombosis), they are not covered in this ECDP.
Figure 1 Scope of the Expert Consensus Decision Pathway on Cardiovascular Sequelae of COVID-19 in Adults PASC = post-acute sequelae of SARS-CoV-2 infection; RTP = return to play; SARS-CoV-2 = severe acute respiratory syndrome coronavirus 2.
…”
Section: Rationalementioning
confidence: 99%
“… 2 , 3 , 4 , 5 Prior studies have reported heterogeneous cardiac manifestations, including myocarditis, 6 , 7 , 8 , 9 , 10 myocardial infarction (MI), 11 , 12 , 13 arrhythmias, 2 , 14 , 15 stress cardiomyopathy, 7 , 16 , 17 and cardiogenic shock. 18 Although the precise pathophysiological mechanisms of myocardial injury remain unclear, 19 it is well established that myocardial injury in patients with COVID-19 is associated with increased morbidity. 20 , 21 It is therefore crucial to better understand the etiologies of myocardial injury in patients with COVID-19, to provide optimal treatment and monitoring for patients.…”
mentioning
confidence: 99%
“… 1 , 2 COVID-19 vaccination is effective in mitigating risk of severe disease and mortality, prompting widespread efforts for implementation, particularly in this high-risk cohort. 3 Still, considerable uncertainty exists regarding optimal strategies for prevention and treatment of COVID-19 in HT candidates and recipients. The purpose of this study was to examine opinions of health-care related personnel and transplant center policies about practices for the prevention and treatment of COVID-19 in HT donors and recipients, with a particular focus on the role of vaccination.…”
Section: Introductionmentioning
confidence: 99%